Internalization Of Multikultural Values In Pondok- Pesantren Education (Study at Pesantren API Tegalrejo Magelang) - Siyono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to reveal how multicultural values are internalized in the API Tegalrejo Magelang Islamic boarding school. This research is field research that uses a qualitative approach. The subjects of this study were the caregivers of pesantren, leaders of pesantren, administrators of pesantren, Ustadz-ustadzah, and students. The data in this study were obtained through interviews, observations, and documentation.The results of this study produced several findings:  firstly multicultural values were internalized as strengthening scientific traditions in Islamic boarding schools.  Second, the process of internalizing multicultural values begins with socialization, assignment, and habituation and ends in assessment.  Third, the passion for multicultural values as a result of the scientific process can strengthen the science of pesantren which is shown by identifying multicultural values as a characteristic of pesantren.